HO ENG DJI: PENYAIR PENCARI TAKDIR - Umi Syam (Fakultas Ilmu Budaya universitas Hasanuddin, 2019)
Hoo Eng Dji became an important figure between 1921 until 1960. He was born from a Chinese family who lived in Maros, not far from Makassar, he then later composed lyrics and poems in Makassarese. His life journey from birth, education and in various modes of life enabled him to read the situations and conditions he experienced and write them in his lyric and poetry. HED lived in three historical periods in the Makassar community in particular and in Indonesia in general. He worked in the colonial period, the Japanese occupation era and in the early stage of the Indonesian nation state. As a Chinese descent, HED learned Makassarese, and made lyric and poetry in that language. These works in the form of lyric and poems in Makassarese expanded his audiences and communicated his ideas to readers and listeners of his works. His ability to reach out to all groups, became a lesson for all Indonesians on the importance of living together collectively without being confined into an identity based on social class, religion and race. Keywords: Hoo Eng Dji, Lyric, Poetry, Makassar, Chinese.